Ameliorated performance of a microbial fuel cell operated with an alkali pre-treated clayware ceramic membrane. (24th June 2020) - Das, Indrasis; Das, Sovik; Sharma, Sahil; Ghangrekar, M.M.
Abstract: Clayware membrane amalgamated with 20% montmorillonite (M-20), acts as an excellent cost effective proton exchange membrane (PEM) for the application in field-scale microbial fuel cells (MFCs). In this investigation, M-20 membrane was pre-treated by acid (M-A), neutral water (M-N) and alkali (M-B), followed by the determination of the membrane properties to access their applicability in MFCs. With alkali treatment of M-20 membrane, maximum proton mass transfer coefficient of 6 × 10 −6 cm s −1 was obtained, which was nearly five times higher than M-A (1.15 × 10 −6 cm s −1 ) and four times higher than the control membrane, M-N. Proton conductivity was also found to be maximum for M-B (17.9 × 10 −3 S cm −1 ), which was four times higher than both M-N (4.4 × 10 −3 S cm −1 ) and M-A (4.6 × 10 −3 S cm −1 ). Oxygen mass transfer coefficient was found to be minimum for M-B (4.02 × 10 −5 cm s −1 ), which was considerably lesser than that observed for M-N (16.2 × 10 −5 cm s −1 ) and M-A (13.8 × 10 −5 cm s −1 ). Cation transport number of M-B (0.15 ± 0.01) was found to be two folds lower than M-N, demonstrating M-B is more selective towards proton transport compared to other cations. The MFC-B with M-B as PEM performed superior as compared with other MFCs, demonstrating coulombic efficiency (CE) of 10.2%, chemical oxygen demand (COD) removal efficiency of 88% and power density of 83.5 mW m −2 . On the other hand, MFCs using M-A and M-N as PEM, demonstrated mediocre performance with CE of 6% and 7.6%, COD removal efficiency of 80% and 83% and power density of 40.4 ± 6.2 mW m −2 and 64.0 ± 5.8 mW m −2, respectively. Hence, alkali treatment of clayware ceramic membrane elucidated its appropriateness for proliferating the efficacy of MFCs and these are recommended for scaling up of MFCs. Graphical abstract: Image 1 Highlights: Alkali treated montmorillonite blended clayware separator shows proton selectivity. Proton conductivity increased four times by alkali treatment. Oxygen diffusion of alkali treated separator was reduced by 4 times. Power density of MFC increased by 1.5 times using alkali treated ceramic separator.